PERCEPTIONS OF NATIONAL EMPLOYEES ON EMIRATIZATION POLICIES IN UAE PRIVATE ORGANIZATIONS - REDDY, ANURADHA (International Journal of Advanced Science and Technology, 2019)
Government of UAE (United Arab Emirates) has emphasized employment of nationals in private sector and to facilitate this process the government made it mandatory for the organizations to employ nationals in government and private sectors. According to the new rule 30 percent of private sector workforce should be UAE nationals but till now only 15 percent of the target could be achieved. On the other hand Emiratis employed in private sector have different perceptions on work related factors in comparison with government organizations. This situation calls for the government and corporate to address this issue on priority. This study aims to identify key issues and may help organizations in formulating appropriate strategies for maintaining balance among employee performance and create a healthy organizational culture that focuses on achieving organizational objectives. Objectives of the study are to (i) identify different factors that nationals perceive toward Emiratization policy, (ii) analyze the impact of work related factors on nationals performance and (iii) identify suitable strategies to overcome the factors effecting. This study was conducted on a sample population of 379 national employees and 196 HR managers working in UAE’s private organizations. Factor analysis is used to identify the critical factors. To test the appropriateness of data and for conducting factor analysis, KMO Measure of Sampling Adequacy and Bartlett Test of Sphericity is performed. Null hypotheses were developed based on chosen factors from literature. Suggestions from the study may help them to overcome the issues and challenges through formulating effective strategies.